Influence of different levels of nitrogen and phosphorus on growth and yield of turmeric (Curcuma longa L.) - Singh, Annie Thomas, Swati Barche, D B (Journal of Spices and Aromatic Crops, 2002)
A nutritional trial on turmeric (Curcuma longa L.) variety Suvarna, conducted with three levels of nitrogen (45, 60 and 75 kg ha-1) and three levels of potassium (90, 120 and 150 kg ha-1) at Horticulture Research Farm, Allahabad Agricultural Institute, indicated that the growth and yield potential of the crop under Allahabad agro climatic condition can be increased by applying NPK at the rate of 75 : 60 : 150 kg ha-1.